The role of astrocytes in the nucleus tractus solitarii in maintaining central control of autonomic function - Martinez, Diana (Am J Physiol Regul Integr Comp Physiol, 2021)
The nucleus tractus solitarii (nTS) is the first central site for the termination and integration of autonomic and respiratory sensory information. Sensory afferents terminating in the nTS as well as the embedded nTS neurocircuitry release and utilize glutamate that is critical for maintenance of baseline cardiorespiratory parameters and initiating cardiorespiratory reflexes, including those activated by bouts of hypoxia. nTS astrocytes contribute to synaptic and neuronal activity through a variety of mechanisms, including gliotransmission and regulation of glutamate in the extracellular space via membrane-bound transporters. Here, we aim to highlight recent evidence for the role of astrocytes within the nTS and their regulation of autonomic and cardiorespiratory processes under normal and hypoxic conditions.